Use of non-antibiotic growth promoter Grow Power in commercial broiler diet (Bangladesh Journal of Animal Science, 2015)
An experiment was conducted with 160, day old Cobb 500 broiler chicks to evaluate the effect of supplementation of Grow Power (GP) on the performance of broiler. The dietary treatments were control (D1), Grow Power (D2), Grow Power plus antibiotic (D3) and antibiotic (D4). At 5th week of age, the body weight of birds at different dietary treatments were 938.75, 1105.00, 1136.25, and 985.00g in the diets of D1, D2, D3 and D4, respectively. Body weight gain at 2nd, 3rd and 4th week of age were significantly (P